The Molecular Pathology of Odontogenic Tumors: Expanding the Spectrum of MAPK Pathway Driven Tumors - Guimarães, Letícia Martins; Coura, Bruna Pizziolo; Gomez, Ricardo Santiago; Gomes, Carolina Cavalieri (Frontiers in Oral Health, 2021)
Odontogenic tumors comprise a heterogeneous group of lesions that arise from the odontogenic apparatus and their remnants. Although the etiopathogenesis of most odontogenic tumors remains unclear, there have been some advances, recently, in the understanding of the genetic basis of specific odontogenic tumors. The mitogen-activated protein kinases/extracellular signal-regulated kinases (MAPK/ERK) pathway is intimately involved in the regulation of important cellular functions, and it is commonly deregulated in several human neoplasms. Molecular analysis performed by different techniques, including direct sequencing, next-generation sequencing, and allele-specific qPCR, have uncovered mutations in genes related to the oncogenic MAPK/ERK signaling pathway in odontogenic tumors. Genetic mutations in this pathway genes have been reported in epithelial and mixed odontogenic tumors, in addition to odontogenic carcinomas and sarcomas. Notably, B-Raf proto-oncogene serine/threonine kinase (BRAF) and KRAS proto-oncogene GTPase (KRAS) pathogenic mutations have been reported in a high proportion of ameloblastomas and adenomatoid odontogenic tumors, respectively. In line with the reports about other neoplasms that harbor a malignant counterpart, the frequency of BRAF p.V600E mutation is higher in ameloblastoma (64% in conventional, 81% in unicystic, and 63% in peripheral) than in ameloblastic carcinoma (35%). The objective of this study was to review MAPK/ERK genetic mutations in benign and malignant odontogenic tumors. Additionally, such genetic alterations were discussed in the context of tumorigenesis, clinical behavior, classification, and future perspectives regarding therapeutic approaches.